Implementation of an Accounting Information System Improving the Quality of Financial Reporting - Ajrina, Ajrina; Hazmi, Yusri; Farisi, Bayu Al; Mauliza, Nurul (The Es Accounting And Finance, 2024)
Information systems play a crucial role in companies and businesses, particularly in accounting information systems. This study centers on the execution of accounting information systems to achieve enhanced quality of financial statements. The research methodology employed in this study is a comprehensive review of existing literature. The data utilized is classified as secondary data. The study findings demonstrate that the use of accounting information systems has a substantial influence on enhancing the accuracy and reliability of financial statements. Furthermore, the effective utilization of accounting information systems is contingent upon the backing of management, which plays a role in enhancing the accuracy and reliability of financial statements.